Adhesion molecules in cerebrovascular diseases: evidence for an inflammatory endothelial activation in cerebral large- and small-vessel disease - Faßbender, Klaus; Bertsch, Thomas; Mielke, Orell; Mühlhauser, Frank; Hennerici, Michael G. (Stroke, 1999)
BACKGROUND AND PURPOSE: Adhesion molecules mediate attachment and transendothelial migration of leukocytes as a critical step in pathogenesis of atherosclerosis. Their expression and release were comparatively investigated in patients with large- and small-vessel disease of the central nervous system. - METHODS: With immunological methods, serum concentrations of endothelial-derived adhesion molecules (soluble endothelial-leukocyte adhesion molecule [sE-selectin], soluble vascular-leukocyte adhesion molecule-1, and soluble intercellular adhesion molecule-1 [sICAM-1]) were quantified in patients with obstructive disease of extracranial (n=89) and intracranial (n=20) large-vessel disease and patients with subcortical vascular encephalopathy (n=64), a cerebral small-vessel disease. As controls, age- and sex-matched subjects without obstructive cerebrovascular disease (n=67) were studied. - RESULTS: We observed significantly increased serum concentrations of sE-selectin and sICAM-1 in patients with both obstructive disease of the large brain-supplying arteries and subcortical vascular encephalopathy. Interestingly, the highest levels were observed in intracranial macroangiopathy. Furthermore, concentrations of sICAM-1 and sE-selectin were significantly increased in current smokers but not in diabetic or hypertensive patients. - CONCLUSIONS: The observation of elevated release of endothelial-derived adhesion molecules in both patients with stenoses of the large brain-supplying arteries and patients with subcortical vascular encephalopathy indicates that inflammatory endothelial activation and adhesion of leukocytes play similarly important roles in cerebral large- and small-vessel disease.